Pengembangan Media Peta Digital Keberagaman Suku di Indonesia untuk Kelas IV Sekolah Dasar - Muhammad Farkhan Sayoga; Puri Selfi Cholifah; Khusnul Khotimah; Muhammad Farkhan Sayoga; Puri Selfi Cholifah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: Today's learning media offers flexibility for users. The development of digital media maps of ethnic diversity in Indonesia was carried out with the aim of producing learning media that received validation from media experts and material experts, media that was practical for teachers to use, and attractive to students in class IV elementary schools. The subjects of this research were fourth grade students at Banjarejo Donomulyo 1 State Elementary School, in January 2023. The ADDIE model was applied in this research in five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments used were observation, interviews and questionnaires. Expert validation on products that have been developed obtained a percentage of 94.44 percent from media experts, and 86.11 percent from material experts. Media products obtained a percentage of 95 percent from practicality trials. And through the results of the attractiveness test, an average percentage of 91.67 percent was obtained from the one-on-one test, 90.71 percent from the small group test, and 94.01 percent from the large group test. Based on these results, the digital media map of ethnic diversity in Indonesia for Class IV Elementary Schools is categorized as valid, practical and interesting. Abstrak: Media pembelajaran masa kini menawarkan fleksibilitas bagi pengguna. Pengembangan media peta digital keberagaman suku di Indonesia dilakukan dengan tujuan menghasilkan media pembelajaran yang mendapatkan validasi dari ahli media serta ahli materi, media yang praktis digunakan oleh guru, dan menarik bagi peserta didik di kelas IV Sekolah Dasar. Subjek dari penelitian ini yaitu peserta didik kelas empat di Sekolah Dasar Negeri 1 Banjarejo Donomulyo, pada Januari 2023. Model ADDIE diterapkan pada penelitian ini dalam lima tahapan yakni Analysis, Design, Development, Implementation, dan Evaluation. Instrumen yang digunakan yaitu observasi, wawancara, dan angket. Validasi ahli pada produk yang telah dikembangkan memperoleh persentase 94,44 persen dari ahli media, dan 86,11 persen dari ahli materi. Produk media memperoleh persentase 95 persen dari uji coba kepraktisan. Serta melalui hasil uji coba kemenarikan diperoleh rerata perentase 91,67 persen dari uji satu lawan satu, 90,71 persen dari uji kelompok kecil, dan 94,01 persen dari uji kelompok besar. Berdasarkan perolehan tersebut media peta digital keberagaman suku di Indonesia untuk Kelas IV Sekolah Dasar termasuk kategori valid, praktis, dan menarik.